Analysis of The Determinants on Technology Share Prices Listed on the Indonesian Stock Exchange in the 2018-2022 period - Vivi Elisa; Setiyo Purwanto (PT Mattawang Mediatama Solution, 2024)
This study aims to examine the effect of The Fed, Inflation and Total Cash Flow on stock prices in the technology sector listed on the Indonesia Stock Exchange for the period 2018-2022. The type of data used in this study is panel data using quantitative methods. The research sample involved six technology companies. Data is collected using company financial reports and macroeconomic data from official sources. The results showed that the Fed and inflation have a negative influence on stock prices. Meanwhile, total cash flow has a positive and significant effect on stock prices.